The Influence of Perceptions of Risks and Benefits on the Continuity of Use of Fintech Services - Artur Barretti Mascarenhas; Cristiane Koda Perpétuo; Erika Borgonovo Barrote; Maria Paula Perides (BBR: Brazilian Business Review)
New technologies have been driving the global financial market, including fintech companies, which provide disruptive financial services in which information technology is the key factor. The objective of this study is to identify which factors most influence intentions to continue using these companies’ products. To achieve this, research by Ryu (2018) was replicated. Our adopted model evaluates the weight of seven factors composing two latent variables - perceived risk and perceived benefit - in the continuity of use of these services. The data collection was performed through an electronic survey, distributed through social networks during May and June of 2019. The main results confirmed seven of the eleven initial hypotheses, highlighting that the perceived benefits, especially the economic ones, were relevant to early adopters and seamless transactions were relevant for late adopters. Surprisingly, perceived risk was not a determinant of continuance intention. One of the contributions of this study is that it indicates some possible demographic and behavioral characteristics of Brazilian fintech consumers, opening up space for a better understanding of the market and service improvements.